A guide to Malaysian takeovers and mergers law - Ambaras Khan, Mushera Bibi (Sweet & Maxwell, Malaysia, 2013)
The takeovers and mergers of companies is a common activity in an active and dynamic equities market. As takeovers and mergers often involve large sums of money and affect many parties, effective regulation of this activity is essential for the healthy operation and confidence of the market. In this regard, regulations and requirements are set out in the Capital Markets and Services Act 2007 and the Malaysian Code on Takeovers and Mergers and compliance with these regulations is supervised by the Securities Commission.